The relationship between perception of social support and fatigue in patients with cancer - Leila Mardanian-Dehkordi; LeilaSadat Kahangi (Wolters Kluwer Medknow Publications, 2018)
Background: Fatigue is one of the most common issues related to cancer. Social support has direct effects on health status and coping with illness. This study investigated the relationship between the perception of social support and fatigue in patients with cancer. Materials and Methods: This descriptive/correlational study was conducted in Omid Hospital in Isfahan, Iran in 2014. One hundred and twenty-five cancer patients receiving chemotherapy were included in the study. Study participants were selected using consecutive sampling. Data were collected using the Cancer Fatigue Scale (CFS), Perceived Social Support Scale, and a demographic characteristics questionnaire. The collected data were analyzed using descriptive and analytical statistical tests in SPSS software. Results: Mean (SD) of patients' fatigue and perceived social support scores were 40.63 (11.59) out of 100 and 49.33 (7.85) out of 100, respectively. The Pearson correlation coefficient showed an inverse relationship between fatigue and social support, however, this relationship was not significant. Multiple regression test was used to detect which dimension of perceived social support was a better predictor of the reduction in fatigue score. This test showed that the best predictor was informational support (B = −0.35, p = 0.004). Conclusions: Results showed a negative relationship between fatigue and perceived social support in cancer patients undergoing chemotherapy. Therefore, social support interventions can help reduce fatigue.